Maternal-fetal cytokine profiles in acute SARS-CoV-2 “breakthrough” infection after COVID-19 vaccination - Packer, Claire H.; Jasset, Olyvia; Hanniford, Nikolina; Brigida, Sara; Demidkin, Stepan; Perlis, Roy H.; Edlow, Andrea G.; Shook, Lydia L. (Frontiers in Immunology, 2025)
ObjectiveVaccination is protective against severe COVID-19 disease, yet whether vaccination reduces COVID-19-associated inflammation in pregnancy has not been established. The objective of this study is to characterize maternal and cord cytokine profiles of acute SARS-CoV-2 “breakthrough” infection (BTI) after vaccination, compared with unvaccinated infection and uninfected controls.Study design66 pregnant individuals enrolled in the MGH COVID-19 biorepository (March 2020-April 2022) were included. Maternal sera were collected from 26 unvaccinated and 21 vaccinated individuals with acute SARS-CoV-2 infection. Cord sera were collected at delivery. Maternal and cord sera from 19 term dyads without current or prior SARS-CoV-2 infection were analyzed as controls. Cytokines were quantified using the Human Inflammation 20-Plex ProcartaPlex assay.ResultsThere was a significantly higher incidence of severe/critical maternal illness in unvaccinated pregnant individuals with SARS-CoV-2 compared to vaccinated (10/26 (38%) vs. 0/21 (0%), p<0.01). Significantly higher maternal levels of TNFα and CD62P were observed in vaccinated individuals with SARS-CoV-2 BTI compared with unvaccinated individuals with infection (p<0.05). Network correlation analyses revealed a distinct maternal cytokine response to SARS-CoV-2 in vaccinated vs unvaccinated individuals. Neither unvaccinated nor vaccinated SARS-CoV-2 infection resulted in elevated cord cytokines compared to controls. Multivariate analyses demonstrate distinct maternal and cord cytokine profiles in the setting of maternal SARS-CoV-2 at delivery.ConclusionVaccination was associated with higher maternal cytokine levels during acute SARS-CoV-2 infection compared to unvaccinated infection, which may reflect vaccine-mediated priming of the immune system. A fetal inflammatory response specific to maternal SARS-CoV-2 infection was not observed.